Hands-On One-shot Learning with Python Learn to implement fast and accurate deep learning models with fewer training samples using PyTorch - Jadon, Shruti (Packt Publishing Limited, 2020)
bGet to grips with building powerful deep learning models using PyTorch and scikit-learn/b h4Key Features/h4 ulliLearn how you can speed up the deep learning process with one-shot learning /li liUse Python and PyTorch to build state-of-the-art one-shot learning models /li liExplore architectures such as Siamese networks, memory-augmented neural networks, model-agnostic meta-learning, and discriminative k-shot learning/li/ul h4Book Description/h4 One-shot learning has been an active field of research for scientists trying to develop a cognitive machine that mimics human learning. With this book, you'll explore key approaches to one-shot learning, such as metrics-based, model-based, and optimization-based techniques, all with the help of practical examples. Hands-On One-shot Learning with Python will guide you through the exploration and design of deep learning models that can obtain information about an object from one or just a few training samples.